2009
DOI: 10.1007/s00426-009-0228-0
|View full text |Cite
|
Sign up to set email alerts
|

Effector identity and orthogonal stimulus–response compatibility in blindness to response-compatible stimuli

Abstract: Perceiving a visual stimulus is hampered when the stimulus is compatible with simultaneously prepared or executed action (blindness effect). We explored the roles of the effector identity of the responding hand and of orthogonal compatibility (above-right/below-left correspondence) in the blindness effect. In Experiment 1, participants conducted bimanual key presses with vertically arranged responses while perceiving a brief presentation of rightward or leftward arrowheads. A blindness effect based on the effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 47 publications
2
10
0
Order By: Relevance
“…Based on the prolonged time course of motorvisual interference, Wühr and Müsseler (2001) have concluded that motorvisual impairment is caused by the binding of perceptual event representations in compound representations of the action plan. This view has now become common sense in motorvisual interference research (Hommel, 2004; Nishimura and Yokosawa, 2010a; Thomaschke et al, 2012b). …”
Section: How Are Perceptual Effect Representations Processed In Actiomentioning
confidence: 91%
See 1 more Smart Citation
“…Based on the prolonged time course of motorvisual interference, Wühr and Müsseler (2001) have concluded that motorvisual impairment is caused by the binding of perceptual event representations in compound representations of the action plan. This view has now become common sense in motorvisual interference research (Hommel, 2004; Nishimura and Yokosawa, 2010a; Thomaschke et al, 2012b). …”
Section: How Are Perceptual Effect Representations Processed In Actiomentioning
confidence: 91%
“…In the majority of motorvisual interference studies, this condition is, however, not met. Usually R1 is executed at leisure after S1, and S2 perception is measured shortly before, shortly after, or during execution of R1 (e.g., Müsseler et al, 2000, 2001; Eder and Klauer, 2007; Nishimura and Yokosawa, 2010a). Under such a scenario, R1 features can be assumed to be long activated and bound when participants initiate the movement and S2 is presented.…”
Section: How Are Perceptual Effect Representations Processed In Actiomentioning
confidence: 99%
“…The lower-ranked internal coding of anatomical identity is influential only when a higher-ranked external positional coding could not be used. Evidence for hierarchical action coding is reported in a wide range of interactions between spatial/spatially-associated stimulus features and manual responses (Klapp et al, 1979; Müller and Schwarz, 2007; Nishimura and Yokosawa, 2010b). …”
Section: Introductionmentioning
confidence: 99%
“…Müsseler and Hommel first described an apparent blindness to response-compatible visual stimuli, calling it action-affected blindness [47]. This effect later was replicated by several studies, all using a very similar method [48,49,50,51,52]. Participants plan left or right keypresses, but, just before they execute the action, an arrow is presented very briefly and they must report whether the arrow is pointing left or right.…”
Section: Actions Influencing Perceptionmentioning
confidence: 99%
“…When motor plans and the perceived stimulus overlap, experiments often report action-blindness effects [47,48,49,50,51,52]; that is, the relative blindness or missed perception of a stimulus that is congruent with the action-plan. Under limited resources, the system should filter out unnecessary information and focus on detecting stimuli that do not match predictions and therefore may require modification of actions.…”
Section: The Case For Predictive Modelsmentioning
confidence: 99%